2019
DOI: 10.9770/jesi.2019.7.2(56)
|View full text |Cite
|
Sign up to set email alerts
|

Expert assessmen of entrepreneurial activity development: a case study

Abstract: This article is devoted to the problem of stimulating the entrepreneurial activity of the population, contributing to the development of the country's economy through new goods and services formation, as well as the development of new industries and markets. The paper presents the results of a study of the business environment of the Republic of Kazakhstan based on expert opinions, namely the factors that can have a stimulating or deterrent effect on the development of the population's entrepreneurial activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…The most important is the lack of financial resources (Belwal et al, 2014;Cavada et al, 2018;Choto et al, 2014;Cristina et al, 2018;Karadzic et al, 2015;Rivetti and Migliaccio, 2015) that is bank loans are rarely provided and constrained by bureaucratic and other barriers. Other important financial challenges are the lack of financial support from the government (Dhewanto et al, 2020;Tleuberdinova et al, 2019), limited profit and limited growth in sales and revenue. Such challenges can inhibit many individuals from taking advantage of the opportunities they see in the market, preventing them from becoming entrepreneurs (Rivetti and Migliaccio, 2015).…”
Section: Msar 32mentioning
confidence: 99%
See 3 more Smart Citations
“…The most important is the lack of financial resources (Belwal et al, 2014;Cavada et al, 2018;Choto et al, 2014;Cristina et al, 2018;Karadzic et al, 2015;Rivetti and Migliaccio, 2015) that is bank loans are rarely provided and constrained by bureaucratic and other barriers. Other important financial challenges are the lack of financial support from the government (Dhewanto et al, 2020;Tleuberdinova et al, 2019), limited profit and limited growth in sales and revenue. Such challenges can inhibit many individuals from taking advantage of the opportunities they see in the market, preventing them from becoming entrepreneurs (Rivetti and Migliaccio, 2015).…”
Section: Msar 32mentioning
confidence: 99%
“…Ceptureanu and Ceptureanu (2015) and Wagdi and Hasaneen (2019) found that the most significant challenges entrepreneurs face are governmental challenges. Governmental challenges include bureaucracy (the restricted rules, regulations and procedures to open and operate your business), high taxation (Rivetti and Migliaccio, 2015;Tleuberdinova et al, 2019), corruption (Rivetti and Migliaccio, 2015;Areiqat et al, 2019), poor government policies (Areiqat et al, 2019), lack of legislative support (Wagdi and Hasaneen, 2019), unstable regulations (Rivetti and Migliaccio, 2015), poor legal environment and lack of tax incentives (Wagdi and Hasaneen, 2019), lack of institutional efficiency (Cavada et al, 2018), lack of security (Alon and Shneor, 2017;Islam et al, 2019), negative attitude (Choto et al, 2014). Islam et al (2019) explained that there is an apparent and biased lack of support for female entrepreneurs from the government.…”
Section: Msar 32mentioning
confidence: 99%
See 2 more Smart Citations
“…Scientists named entrepreneurship "a dictator of economic life" (Bratnicki, 2002), as well as "an engine of economic growth" (Baron & Shane, 2008) or "integral part of economic change and growth" (Parker, 2018). An entrepreneur is mostly considered a person who is doing something innovative, something new, who provides resources for creating new opportunities, but it also means that an entrepreneur (not only as a founder of a business) can explore new markets for existing products, or new ways of doing something more efficiently (Tleuberdinova et al, 2019). Entrepreneurial employees may also be more effective at their work and bring added value to a company.…”
mentioning
confidence: 99%